Indoor soundscape, speech perception, and cognition in classrooms: A systematic review on the effects of ventilation-related sounds on students. (15th May 2023) - Pellegatti, Matteo; Torresin, Simone; Visentin, Chiara; Babich, Francesco; Prodi, Nicola
Abstract: Good air quality in classrooms, achieved through natural or mechanical ventilation, is necessary for students' health and cognition, but might simultaneously expose them to challenging sound environments, affecting learning and well-being. In this work we focused on the interaction between acoustics and ventilation modality and systematically reviewed the effects of sound stimuli related to ventilation on students' speech perception, cognition, and acoustic comfort. Adopting the PRISMA guidelines, we selected 37 studies published after 1990, including students from primary school to university and assessing the impacts either of fan noise from mechanical ventilation or of sounds intruding into the classroom when windows are opened (i.e. traffic noise, aircraft noise, railway noise, human noise, sirens and construction noise, natural sounds). By comparison with a quiet baseline condition (no noise or low sound level), the effects were categorized as positive, null or negative. Our systematic review showed a negative effect of fan noise. However, future research should better frame the result by including an integrated approach between acoustical and ventilation requirements. Concerning anthropogenic sounds entering the classroom in natural ventilation conditions, negative or no effects were generally observed, depending on the specific task and noise characteristics. On the contrary, natural sounds from open windows were found to consistently yield a positive effect on students' learning and comfort. Therefore, ventilation can sometimes improve the indoor soundscape depending on the context. The limitations of the currently available knowledge and under-investigated areas were outlined through the systematic review, which should be addressed in future studies. Highlights: Reviewing the combined effect of acoustic and ventilation on students in classrooms. Noise from mechanical ventilation is critical for students' performance and comfort. The effect of anthropogenic noises depends on the sound type and the task-at-hand. Natural sounds have positive effects and may be used to shape classrooms soundscape.